2011
DOI: 10.1007/s10047-011-0596-2
|View full text |Cite
|
Sign up to set email alerts
|

Variations in local elastic modulus along the length of the aorta as observed by use of a scanning haptic microscope (SHM)

Abstract: Variations in microscopic elastic structures along the entire length of canine aorta were evaluated by use of a scanning haptic microscope (SHM). The total aorta from the aortic arch to the abdominal aorta was divided into 6 approximately equal segments. After embedding the aorta in agar, it was cut into horizontal circumferential segments to obtain disk-like agar portions containing ring-like samples of aorta with flat surfaces (thickness, approximately 1 mm). The elastic modulus and topography of the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…A recent report of an automated method for quantifying collagen fiber orientation in thick-walled blood vessels will allow such investigations to be performed with relative ease [31] The deformation of the aorta is considered axisymmetric. Recent studies have shown that the mechanical properties of porcine thoracic aorta vary not only longitudinally but also circumferentially, which means that the stress and strain fields are not axisymmetric [32]. Accounting for this fact requires the formulation and quantification of a more general class of strain energy functions that include shear strain components and possible mechanical nonhomogeneity.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report of an automated method for quantifying collagen fiber orientation in thick-walled blood vessels will allow such investigations to be performed with relative ease [31] The deformation of the aorta is considered axisymmetric. Recent studies have shown that the mechanical properties of porcine thoracic aorta vary not only longitudinally but also circumferentially, which means that the stress and strain fields are not axisymmetric [32]. Accounting for this fact requires the formulation and quantification of a more general class of strain energy functions that include shear strain components and possible mechanical nonhomogeneity.…”
Section: Discussionmentioning
confidence: 98%
“…In a separate study, we are developing a scanning haptic microscope that can observe the precise distribution of the elastic modulus on a cross-sectional surface of the tissue. 16,17 This is accomplished by segregating the elastin-rich and collagen-rich areas on the aortic tissue. Therefore, the differences in the density or the orientation of the collagen fibers, between the conduit and leaflet parts, will be obvious.…”
Section: Discussionmentioning
confidence: 99%
“…These data were consistent with the tendency of elastic fiber density distribution observed by histological staining section of the aorta. They also revealed microscopically the elastic modulus of the aorta [29].…”
Section: Blood Vessel Prosthesismentioning
confidence: 98%